UTILIZATION OF QUIZIZZ LEARNING MEDIA FOR BASIC EDUCATION LEVEL LEARNING IN HAPPY CITY - Dian Erlita; Akmaluddin; Siti Mayang sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
In essence, education is a basic right for every Indonesian citizen to beable to enjoy it. Education is a conscious effort made by humans in orderto develop their potential through the learning process. The existence ofthis very important education has been recognized and at the same timehas very strong legality as stated in the 1945 Constitution article 31 (1)which states that every citizen has the right to education. This researchwas conducted in class VI of Ujong Gunong Public Elementary School,Kota Happy District. The research was conducted for two weeks. Thesubjects of this study were 5 students in class VI at Ujong GunongPublic Elementary School, Kota Happy District. The first indicator thatresearchers use is compatibility with the goals to be achieved. Theteacher's perception of the media based on these indicators, the teacherfeels that the use of Quizizz as a learning medium is in accordance withthe learning objectives to be achieved. This is due to the use of Quizizzwhich can be set based on the learning objectives to be achieved. Forschools, especially teachers, it is necessary to carry out learninginnovations according to needs and continuously to improve the learningprocess as well as fostering the teaching profession, so that learningproblems can be resolved. The application of Quizizz educational gamebased learning media is only one alternative solution in improvingstudent learning outcomes, especially elementary school students.